ANALISIS DAMPAK PENGGUNAAN UANG ELEKTRONIK (E-MONEY) PADA PERILAKU KONSUMTIF IBU RUMAH TANGGA - safira nurul fatohah; Vania Zulfa; Shinta Doriza (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2023)
The purpose of this study was to determine the effect of using electronic money on consumptive behavior in housewives. This research method is associative quantitative. The subject of the study was a housewife in Caringin Subdistrict. Data collection techniques use instruments in the form of questionnaires. The sampling technique used is purposive sampling with a total sample of 100 respondents. The percentage of the majority consumptive behavior category in the low category was 76% of respondents. Furthermore, the percentage of the category of using electronic money is mostly in the moderate category was 59% of respondents. The results showed that there was an influence between the use of electronic money on consumptive behavior in housewives in Caringin District with a p-value of 0.001, meaning that the use of electronic money had a significant effect on consumptive behavior but had a low correlation with the contribution of the electronic money use variable of 10.8% to the consumptive behavior variable and the remaining 89.2% was influenced by other variables.